A unique case of spontaneous intestinal volvulus in a pet rabbit (VETERINARIA, 2020)
A ten-month-old male pet rabbit was referred to the Surgery Clinic of the University of Sarajevo Faculty of Veterinary Medicine with the history of several days gradual loss of appetite, decreased defecation frequency and the weight loss. Physical examination revealed low body condition score, tachypnea, tachycardia and distended abdomen painful on palpation. Abdominal radiographs were unremarkable displaying abdominal distention with gas accumulation in the intestines. Urgent explorative celiotomy was performed, and definitive diagnosis of intestinal volvulus was maded. Manual reposition of the intestines secured reestablishment of the intestinal blood flow, and after the observation of intestinal peristalsis the abdomen was closed in a routine fashion. Analgesics, antibiotics and supportive therapy were administered over the next seven days, and the case was finally concluded 14 days post-surgery without any complications detected. To the best of our knowledge, this is the first report of spontaneous intestinal volvulus in a pet rabbit diagnosed by exploratory laparotomy and successfully surgically resolved.
Keywords: gastrointestinal stasis; distended abdomen; gas accumulation; surgical therapy